The health diplomacy spiral: a conceptual framework linking health system integration and public health diplomacy - Aurimas Peckauskas; Arunas Dulkys; Olegas Niaksu; Ramune Kalediene (Public Health Reviews, 2026)
Objectives To examine the interrelations between health system integration, digital transformation and public health diplomacy and to conceptualise how systemic threats, interdependence, and governance constraints shape cross-border health coordination. Methods A structured integrative literature review was conducted in PubMed (2015–2025), covering two domains: health system transformation and health diplomacy. Studies were selected through multi-stage screening. Thematic and conceptual synthesis was used to identify cross-domain patterns. Results The review supported a conceptual synthesis linking systemic pressures, institutional reforms, integration processes, and cross-border coordination. Although these relationships were rarely examined directly in the included studies, cross-domain interpretation suggested convergence through interdependence driven by integration and digitalisation, alongside governance constraints that limit coordination. These conditions may create the structural basis for public health diplomacy as a practice-oriented response to transnational health risks. Conclusion This study proposes the Health Diplomacy Spiral, a conceptual framework for examining how health system integration and digital transformation may generate interdependence and governance complexity. The framework offers an analytical lens for future empirical research on health system transformation, data governance, and international coordination.